Noninvasive fetal RHD genotyping by microfluidics digital PCR using maternal plasma from two alloimmunized women with the variant RHD(IVS3+1G>A) allele. (19th September 2013) - Tsui, Nancy B. Y.; Hyland, Catherine A.; Gardener, Glenn J.; Danon, David; Fisk, Nicholas M.; Millard, Glenda; Flower, Robert L.; Dennis Lo, Y. M.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Noninvasive prenatal RHD typing can be achieved by using cell‐free fetal DNA in the plasma of RhD‐negative mothers. For RhD‐negative mothers carrying intact but dysfunctional RHD gene variants, the abundant maternal RHD sequences in maternal plasma could interfere with the fetal RHD allele detection. What does this study add? Digital PCR provides a high analytical specificity to noninvasively determine the fetal inheritance of RHD allele in alloimmunized pregnancies involving maternal RHD variants.